2019
DOI: 10.1063/1.5088932
|View full text |Cite
|
Sign up to set email alerts
|

Swarm intelligence inspired cooperation promotion and symmetry breaking in interdependent networked game

Abstract: The evolution of a cooperative strategy on multilayer networks is arousing increasing concern. Most of the previous studies assumed that agents can only choose cooperation or defection when interacting with their partners, whereas the actual provisions in real world scenarios might not be discrete, but rather continuous. Furthermore, in evolutionary game, agents often make use of their memory which keeps the most successful strategy in the past, as well as the best current strategy gained by their directed nei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…In this way a strategy-neutral microscopic rule has a biased impact on the competition of strategies. We note that this observation fits nicely to the general concept when there is a non-trivial consequence of a neutral intervention on strategy evolution [46,12,47,48,49,50,51].…”
Section: Resultssupporting
confidence: 79%
“…In this way a strategy-neutral microscopic rule has a biased impact on the competition of strategies. We note that this observation fits nicely to the general concept when there is a non-trivial consequence of a neutral intervention on strategy evolution [46,12,47,48,49,50,51].…”
Section: Resultssupporting
confidence: 79%
“…Fixed networks also show asymmetric results with some parameter values. Previous studies have also reported symmetry breaking on static networks [40][41][42]. However, as Figure 2 shows, this result occurs only with a limited combination of parameter values and the effects are small compared to those observed with link updating.…”
Section: Resultsmentioning
confidence: 67%
“…Moreover, such disparity over networks appears not only at the individual level but also at the macroscopic level; interdependent networks show symmetry breaking by which the overall cooperation levels in each layer diverge. Thus, although the same rules may be applied across the network, the extent of cooperation enhancement can differ across layers [40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Evolution of strategy in a single population [12][13][14][15][16][17][18][19][20][21][22][23] does not generate the difference in payoffs among the players in principle, where the strategy is selected within the same group. Evolution in multi-population [24][25][26][27][28][29] (i.e., intra-group selection of strategies by the inter-group game) and learning among multi-agent [30][31][32][33][34][35][36][37] can generate the exploitation, but so far most studies have focused only on the emergence of cooperation. Recently, the exploitation has been studied as to "symmetry" breaking of the payoffs of players [26,34], where only the game between the same class of strategies is assumed.…”
Section: Introductionmentioning
confidence: 99%